50 años de institucionalización de la licenciatura en química en Colombia: Hacia un estudio histórico necesario en la UPN - Franco-Moreno, Ricardo Andrés (Revista Científica, 2019)
With regard to the commemoration of the 50 years of existence of the Department of Chemistry of the Universidad Pedagógica Nacional and recognizing the need to analyze the processes of institutionalization of the training of graduates in chemistry in the country, based on indicators such as the existence of programs of specific training in the area, this article presents part of the results of a documentary research project aimed at the historical analysis of the dynamics of Bachelor's programs in Chemistry and in scientific fields related to this discipline in the country, during the period 1970-2019. Previous mapping of the situation of training programs for chemistry professors in Latin America and the Caribbean, the documentary study was conducted by tracking information about the training programs available in the databases of the National Information System on Higher Education - SNIES and the analysis of own documents of said programs, orienting this way the methodological route for the necessary study of the program of Degree in Chemistry of the National Pedagogical University. It is concluded that in Colombia the training of graduates in chemistry has attracted the attention of official and private institutions, especially during the 1980s and 1990s, gradually diminishing the training programs in this field during the almost two decades that have elapsed in the 21st century